A biologically active dental implant and its preparation process
By sandblasting, acid etching and alkali leaching on the surface of the dental implant, and combining materials such as chitosan, aldehyde-modified dextran and polyether ether ketone, a biologically active dental implant was formed, which solved the problem of the current situation. The problem of insufficient biological activity of dental implants significantly improves the healing speed and bone stability after implantation.
Patent Information
- Application Number
- CN202411195808.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-29
Smart Images

Figure BDA0005016344930000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of implants, in particular to a dental implant with biological activity and a preparation process thereof. Background Art
[0002] This year, with the development of oral medicine, dental implant restoration technology has gradually become a conventional dental restoration method, which has greatly improved the effect of tooth restoration and the quality of life of patients. At present, the main material of dental implants is titanium alloy, but there are still obvious tissue differences between titanium alloy implants and natural teeth, especially during implantation. Due to the insufficient biological activity on the surface of titanium alloy materials, the lack of connective tissue connections and vascular pathways, it often requires a long slow healing period after implantation. At the time of implantation, due to the large number of bacteria in the oral cavity, the implant is prone to bacterial contamination in the early stage of implantation, causing bacteria to react with human cells on the surface of dental implants to form bacterial biofilms, further hindering the implantation of dental implants. Summary of the invention
[0003] The object of the present invention is to provide a dental implant with biological activity and a preparation process thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a dental implant with biological activity, comprising the following steps:
[0005] S1. Preparing a dental implant blank;
[0006] S11. After the titanium alloy rod is processed into a blank shape, it is polished, washed in a Micro90 cleaning agent for 2-3 times, ultrasonically cleaned with deionized water for 2-3 times, and after constant weight in vacuum drying, the surface is sandblasted. After the sandblasting is completed, a pretreated dental implant blank is obtained;
[0007] S12. Place the pretreated dental implant blank in an acid solution, heat it to 50-90°C, soak it for 10-25 minutes, take it out, wash its surface 2-3 times with deionized water, Micro90 cleaning agent, and ultrapure water respectively, place it again in a 3-6 mol / L sodium hydroxide solution, heat it to 50-80°C, treat it for 24-36 hours, take it out, wash its surface 2-3 times with deionized water, Micro90 cleaning agent, and ultrapure water respectively, dry it to constant weight, and obtain a dental implant blank;
[0008] S2. Preparation of bioactive dental implants;
[0009] S21. Immerse the dental implant blank in a chitosan solution with a concentration of 2-5 g / L, heat to 45-50° C., immerse for 10-60 min, take out, wash the surface with ultrapure water 2-3 times, and set aside;
[0010] S22. Mix the dextran with ultrapure water, stir and mix at room temperature for 12-24 hours, add potassium periodate thereto, react in the dark for 24-48 hours, add ethylene glycol, continue to react in the dark for 1-2 hours, freeze-dry, wash the reaction product 1-2 times with ultrapure water at a temperature of 2-4° C., and freeze-dry again to obtain aldehyde-modified dextran;
[0011] S23. Disperse the aldehyde-modified dextran in a PBS buffer solution, stir and mix at room temperature for 5-10 hours, add the dental implant blank treated in step S21, and react with ultrasonic vibration for 6-12 hours, remove the dental implant blank, and wash its surface with PBS buffer solution and ultrapure water for 2-3 times respectively, blow dry with nitrogen gas, and set aside;
[0012] S24. Mix polyetheretherketone and dimethyl sulfoxide, raise the temperature to 45-50°C, stir and mix for 4-12 hours, add nanohydroxyapatite, ultrasonically mix for 4-12 hours, add the dental implant blank treated in step S23 and immerse it, using an energy density of 250-300mJ / cm 3 After irradiating with ultraviolet light for 30-60 minutes, the dental implant body is taken out and placed in a dimethyl sulfoxide solution containing vinylphosphonic acid. After continuing the irradiation treatment for 5-15 minutes, the dental implant body is taken out, the surface is rinsed with pure dimethyl sulfoxide for 2-3 times, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0013] Furthermore, in step S11, during the sandblasting process, titanium oxide particles are used as the sandblasting material, the particle size of the titanium oxide particles is 50-100 μm, the sandblasting pressure is 2-8 bar, the spraying distance is 40-120 mm, and the sandblasting time is 15-45 s.
[0014] Further, in step S12, the acid solution is prepared by mixing sulfuric acid solution, hydrochloric acid solution and water in a volume ratio of (3-5): (1-4): (4-6);
[0015] Wherein, the concentration of the sulfuric acid solution is 45-98wt%; the concentration of the hydrochloric acid solution is 15-30wt%.
[0016] Further, in step S21, the chitosan concentration in the chitosan solution is 2-5 g / L, and the acetic acid concentration is 2-3 wt %;
[0017] The chitosan has a deacetylation degree of 80-95% and a Mw of 1000-2000 kDa.
[0018] Furthermore, in S22, the dextran Mw is 15-25Kda.
[0019] Furthermore, in step S22, the mass ratio of dextran to potassium periodate and ethylene glycol is 1:(1.1-1.35):(0.45-0.5).
[0020] Furthermore, in step S23, the mass ratio of the aldehyde-modified dextran to the PBS buffer solution is (0.15-0.5):100 in parts by weight.
[0021] Furthermore, in step S23, the mass ratio of polyetheretherketone, nano-hydroxyapatite and vinylphosphonic acid is 10:(2-5):(1-4) in parts by weight.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] In order to improve the biological activity of the dental implant, the present invention firstly performs a modification treatment on the surface of the dental implant blank, generates a honeycomb structure on the surface of the titanium alloy by sandblasting, acid etching and alkali immersion on the titanium alloy surface, performs a honeycomb treatment on the surface morphology, increases the surface area, and performs an activation treatment on the surface, thereby increasing the hydrophilicity of the titanium alloy material;
[0024] On this basis, the present invention further uses chitosan solution to treat dental implant materials, and introduces chitosan materials with positive charges and amino groups on the surface of the dental implant materials. Chitosan materials are excellent natural antibacterial polysaccharides, and the introduction of their positive charges can adsorb negatively charged osteoblasts, thereby promoting the adsorption of osteoblasts on the surface of dental implants and accelerating the early healing of dental implants.
[0025] At the same time, the present invention also performs oxidation treatment on dextran by potassium periodate, introduces aldehyde groups therein, and reacts it with a dental implant with a chitosan structure. The aldehyde groups react with the amino groups in the chitosan, thereby introducing aldehyde groups on the surface of the dental implant. On this basis, the dental implant with aldehyde groups is placed in a polyetheretherketone solution. Under ultraviolet light irradiation, the benzophenone units in the polyetheretherketone form semi-benzopinacol free radicals, which participate in aldehyde reaction grafting, thereby generating a polyetheretherketone film on the surface of the dental implant. In this process, nano-hydroxyapatite with bioaffinity is simultaneously introduced into the polyetheretherketone film, thereby ensuring that there is a gap distance of more than 1 nm between the dental implant and the natural tooth, thereby maintaining the stability of the bone around the implant. Moreover, since the hydrophilicity of polyetheretherketone itself is relatively poor, the present invention also uses vinylphosphonic acid to further participate in the irradiation reaction, thereby introducing hydrophilic phosphate groups on the surface of the polyetheretherketone film, thereby enhancing the bioaffinity. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The chitosan used in this application has a deacetylation degree of 90% and a Mw of 1500 kDa; the nano-hydroxyapatite used has a particle size of 20-200 nm; the polyetheretherketone used is 021G polyetheretherketone;
[0028] Embodiment 1. A method for preparing a dental implant having biological activity, comprising the following steps:
[0029] S1. Preparing a dental implant blank;
[0030] S11. After the titanium alloy rod is processed into a blank shape, it is polished, cleaned in Micro90 cleaning agent for 3 times, ultrasonically cleaned with deionized water for 3 times, and vacuum dried to constant weight, and the surface is sandblasted. Titanium oxide particles are used for sandblasting. The particle size of the titanium oxide particles is 50-100 μm. The sandblasting pressure is 6 bar, the spraying distance is 60 mm, and the sandblasting time is 30 s. After the sandblasting is completed, a pretreated dental implant blank is obtained;
[0031] S12. The pretreated dental implant blank is placed in an acid solution, heated to 70°C, soaked for 18 minutes, taken out, and its surface is washed three times with deionized water, Micro90 cleaning agent, and ultrapure water respectively. It is then placed in a 5 mol / L sodium hydroxide solution again, heated to 75°C, treated for 24 hours, taken out, and its surface is washed twice with deionized water, Micro90 cleaning agent, and ultrapure water respectively. After drying to constant weight, a dental implant blank is obtained;
[0032] The acid solution is prepared by mixing 65wt% sulfuric acid, 30wt% hydrochloric acid and deionized water in a volume ratio of 3:2:4;
[0033] S2. Preparation of bioactive dental implants;
[0034] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0035] Wherein, the chitosan content in the chitosan solution is 2 g / L, and the acetic acid concentration is 3 wt%;
[0036] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.1 parts of potassium periodate was added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol was added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0037] S23. Disperse 0.15 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and ultrasonically vibrate and react for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0038] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 2 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0039] Embodiment 2. A method for preparing a dental implant having biological activity, comprising the following steps:
[0040] Compared with Example 1, this example increases the chitosan concentration in step S21;
[0041] S2. Preparation of bioactive dental implants;
[0042] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0043] Wherein, the chitosan content in the chitosan solution is 5 g / L, and the acetic acid concentration is 3 wt%;
[0044] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.1 parts of potassium periodate was added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol was added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0045] S23. Disperse 0.15 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and ultrasonically vibrate and react for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0046] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 2 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0047] Embodiment 3. A method for preparing a dental implant having biological activity, comprising the following steps:
[0048] Compared with Example 2, this embodiment increases the amount of potassium periodate added in step S22;
[0049] S2. Preparation of bioactive dental implants;
[0050] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0051] Wherein, the chitosan content in the chitosan solution is 5 g / L, and the acetic acid concentration is 3 wt%;
[0052] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.35 parts of potassium periodate were added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol were added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0053] S23. Disperse 0.15 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and ultrasonically vibrate and react for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0054] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 2 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0055] Embodiment 4. A method for preparing a biologically active dental implant, comprising the following steps:
[0056] Compared with Example 3, this example increases the amount of aldehyde-modified dextran added in step S23;
[0057] S2. Preparation of bioactive dental implants;
[0058] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0059] Wherein, the chitosan content in the chitosan solution is 5 g / L, and the acetic acid concentration is 3 wt%;
[0060] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.35 parts of potassium periodate were added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol were added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0061] S23. Disperse 0.5 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and react with ultrasonic vibration for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0062] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 2 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0063] Embodiment 5. A method for preparing a dental implant having biological activity, comprising the following steps:
[0064] Compared with Example 4, this embodiment increases the amount of nano-hydroxyapatite added in step S24;
[0065] S2. Preparation of bioactive dental implants;
[0066] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0067] Wherein, the chitosan content in the chitosan solution is 5 g / L, and the acetic acid concentration is 3 wt%;
[0068] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.35 parts of potassium periodate were added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol were added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0069] S23. Disperse 0.5 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and react with ultrasonic vibration for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0070] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 5 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0071] Embodiment 6. A method for preparing a biologically active dental implant, comprising the following steps:
[0072] Compared with Example 5, this example increases the amount of vinylphosphonic acid added in step S24;
[0073] S2. Preparation of bioactive dental implants;
[0074] S21. Immerse the dental implant blank in the chitosan solution, heat it to 45-50° C., immerse it for 10-60 min, take it out, wash the surface with ultrapure water 2-3 times, and set it aside;
[0075] Wherein, the chitosan content in the chitosan solution is 5 g / L, and the acetic acid concentration is 3 wt%;
[0076] S22. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.35 parts of potassium periodate were added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol were added, and the mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2°C, and then freeze-dried again to obtain aldehyde-modified dextran;
[0077] S23. Disperse 0.5 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S21, and react with ultrasonic vibration for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0078] S24. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 5 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S23 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 4 parts of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0079] Comparative Example 1. A method for preparing a dental implant having biological activity, comprising the following steps:
[0080] Compared with Example 1, this comparative example only carried out step S1 processing;
[0081] S1. Preparation of dental implants;
[0082] S11. After the titanium alloy rod is processed into a blank shape, it is polished, cleaned in Micro90 cleaning agent for 3 times, ultrasonically cleaned with deionized water for 3 times, and vacuum dried to constant weight, and the surface is sandblasted. Titanium oxide particles are used for sandblasting. The particle size of the titanium oxide particles is 50-100 μm. The sandblasting pressure is 6 bar, the spraying distance is 60 mm, and the sandblasting time is 30 s. After the sandblasting is completed, a pretreated dental implant blank is obtained;
[0083] S12. The pretreated dental implant blank is placed in an acid solution, heated to 70°C, soaked for 18 minutes, taken out, and its surface is washed three times with deionized water, Micro90 cleaning agent, and ultrapure water respectively. It is then placed in a 5 mol / L sodium hydroxide solution again, heated to 75°C, treated for 24 hours, taken out, and its surface is washed twice with deionized water, Micro90 cleaning agent, and ultrapure water respectively. After drying to constant weight, a dental implant is obtained;
[0084] The acid solution is prepared by mixing 65wt% sulfuric acid, 30wt% hydrochloric acid and deionized water in a volume ratio of 3:2:4.
[0085] Comparative Example 2. A method for preparing a dental implant having biological activity, comprising the following steps:
[0086] Compared with Example 1, this embodiment only performs step S2 processing;
[0087] S1. Preparation of bioactive dental implants;
[0088] S11. After the titanium alloy rod is processed into a blank shape, it is polished, washed in Micro90 cleaning agent for 3 times, ultrasonically cleaned with deionized water for 3 times, and vacuum dried to constant weight, and the dental implant blank is immersed in chitosan solution, heated to 45-50° C. and immersed for 10-60 minutes, taken out, and the surface is washed with ultrapure water for 2-3 times, and then set aside;
[0089] Wherein, the chitosan content in the chitosan solution is 2 g / L, and the acetic acid concentration is 3 wt%;
[0090] S12. By weight, 1 part of dextran was mixed with 80 parts of ultrapure water, stirred and mixed at room temperature for 12 hours, 1.1 parts of potassium periodate was added thereto, and the mixture was reacted in the dark for 24 hours, and 0.45 parts of ethylene glycol was added thereto. The mixture was reacted in the dark for 2 hours, and then freeze-dried. The reaction product was washed once with ultrapure water at a temperature of 2° C., and then freeze-dried again to obtain aldehyde-modified dextran;
[0091] S13. Disperse 0.15 parts of aldehyde-modified dextran in 100 parts of PBS buffer solution by weight, stir and mix at room temperature for 5 hours, add the dental implant body treated in step S11, and react with ultrasonic vibration for 6 hours. Then, take out the dental implant body, wash its surface twice with PBS buffer solution and ultrapure water respectively, blow dry with nitrogen gas, and set aside;
[0092] S14. 10 parts of polyetheretherketone and dimethyl sulfoxide were mixed, heated to 45°C, stirred and mixed for 8 hours, 2 parts of nanohydroxyapatite were added thereto, ultrasonically mixed for 4 hours, and then the dental implant blank treated in step S13 was added and immersed, using an energy density of 250mJ / cm 3 After irradiating with ultraviolet light for 45 minutes, the dental implant body was taken out and placed in a dimethyl sulfoxide solution containing 1 part of vinylphosphonic acid. After continuing the irradiation treatment for 5 minutes, the dental implant body was taken out, the surface was rinsed twice with pure dimethyl sulfoxide, and then dried by nitrogen purge to obtain a dental implant with biological activity.
[0093] Testing: Using a contact angle measuring instrument to test the surface contact angles of the dental implants prepared in Examples 1-6 and Comparative Examples 1-2;
[0094] The freeze-dried strain of Porphyromonas gingivalis was inoculated into CDC anaerobic blood agar medium and uploaded to the third generation. It was identified as a pure culture by morphology. The freeze-dried strain of Porphyromonas gingivalis was inoculated into BHI liquid medium and cultured at 37°C for 2 days. Then, it was diluted to a density of 1*10 6 cfu / mL bacterial solution, and respectively implanted it on the surface of the dental implants prepared in Examples 1-6 and Comparative Examples 1-2 and a blank sample. After culturing in an anaerobic incubator for 12 hours, the dental implant samples were washed with 5 mL of BHI liquid culture medium and 45 mL of sterile water, and the obtained eluate was inoculated onto a BHI plate and evenly spread. After anaerobic incubation for 12 hours, the plate counts were calculated to calculate the antibacterial rate;
[0095] The antibacterial rate calculation formula is as follows:
[0096] Antibacterial rate = (the number of colonies in the blank sample group - the number of colonies in the experimental group) / the number of colonies in the blank sample group × 100%;
[0097] The dental implants prepared in Examples 1-6 and Comparative Examples 1-2 were placed in 75% ethanol for disinfection for 2 h, and then placed in a 24-well plate. Each well of the 24-well plate was inoculated with 0.5 mL of osteoblast fluid in the logarithmic growth phase, and the cell density was 1*10 7 / L, after culturing for 1, 3, and 7 days, the dental implants were rinsed 3 times with PBS buffer, and then transferred to a new 24-well plate. 0.5 mL of fresh culture medium and 0.05 mL of CCK-8 solution were added in a dark environment at room temperature. After culturing at 37 °C for 2 h, 0.2 mL of the reaction solution was taken from each well and placed in an ELISA reader. The absorbance was detected by 450 nm ultraviolet light, and the osteoblast status was observed under a microscope.
[0098]
[0099] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a biologically active dental implant, characterized in that: The following steps are involved: S1. Preparing a dental implant blank; S11. After the titanium alloy rod is processed into a blank shape, it is polished, washed in a Micro90 cleaning agent for 2-3 times, ultrasonically cleaned with deionized water for 2-3 times, and after constant weight in vacuum drying, the surface is sandblasted. After the sandblasting is completed, a pretreated dental implant blank is obtained; Among them, during the sandblasting process, titanium oxide particles are used as the sandblasting material, the particle size of the titanium oxide particles is 50-100 μm, the sandblasting pressure is 2-8 bar, the spraying distance is 40-120 mm, and the sandblasting time is 15-45 s; S12. The pretreated dental implant blank is placed in an acid solution, heated to 50-90°C, soaked for 10-25 minutes, taken out, and its surface is washed 2-3 times with deionized water, Micro90 cleaning agent, and ultrapure water respectively, and then placed in a 3-6 mol / L sodium hydroxide solution again, heated to 50-80°C, treated for 24-36 hours, taken out, and its surface is washed 2-3 times with deionized water, Micro90 cleaning agent, and ultrapure water respectively, and dried to constant weight to obtain a dental implant blank; The acid solution is prepared by mixing sulfuric acid solution, hydrochloric acid solution and water in a volume ratio of (3-5): (1-4): (4-6); The concentration of the sulfuric acid solution is 45-98wt%; the concentration of the hydrochloric acid solution is 15-30wt%; S2. Preparation of bioactive dental implants; S21. Immerse the dental implant blank in a chitosan solution with a concentration of 2-5 g / L, heat to 45-50° C., immerse for 10-60 min, take out, wash the surface with ultrapure water 2-3 times, and set aside; Wherein, the chitosan concentration in the chitosan solution is 2-5 g / L, and the acetic acid concentration is 2-3 wt%; The chitosan has a deacetylation degree of 80-95% and a Mw of 1000-2000 kDa; S22. Mixing dextran with ultrapure water, stirring and mixing at room temperature for 12-24 hours, adding potassium periodate thereto, reacting in the dark for 24-48 hours, adding ethylene glycol, continuing to react in the dark for 1-2 hours, freeze-drying, washing the reaction product 1-2 times with ultrapure water at a temperature of 2-4° C., and freeze-drying again to obtain aldehyde-modified dextran; Wherein, the mass ratio of the dextran to potassium periodate and ethylene glycol is 1:(1.1-1.35):(0.45-0.5); The dextran Mw is 15-25Kda; S23. The aldehyde-modified dextran is dispersed in a PBS buffer solution, stirred and mixed at room temperature for 5-10 hours, and then the dental implant body treated in step S21 is added. After ultrasonic vibration reaction for 6-12 hours, the dental implant body is removed, and the surface is cleaned 2-3 times with a PBS buffer solution and ultrapure water, respectively, and then dried with nitrogen gas for later use; S24. Mix polyetheretherketone and dimethyl sulfoxide, raise the temperature to 45-50°C, stir and mix for 4-12 hours, add nanohydroxyapatite thereto, ultrasonically mix for 4-12 hours, add the dental implant blank treated in step S23 and immerse it, using an energy density of 250-300mJ / cm 3 After irradiating with ultraviolet light for 30-60 minutes, the dental implant body is taken out and placed in a dimethyl sulfoxide solution containing vinylphosphonic acid. After continuing the irradiation treatment for 5-15 minutes, the dental implant body is taken out, the surface is rinsed with pure dimethyl sulfoxide for 2-3 times, and then dried by nitrogen purge to obtain a dental implant with biological activity.
2. The method for preparing a bioactive dental implant according to claim 1, characterized in that: In step S23, the mass ratio of the aldehyde-modified dextran to the PBS buffer solution is (0.15-0.5):100 in parts by weight.
3. The method for preparing a bioactive dental implant according to claim 1, characterized in that: In step S23, the mass ratio of polyetheretherketone, nano-hydroxyapatite and vinylphosphonic acid is 10:(2-5):(1-4) in parts by weight.
4. A dental implant with biological activity prepared by the preparation method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Poly(ether-ether-ketone) / nano hydroxyapatite dental implant and manufacturing method thereof
CN104906635A
Preparation method of implant active surface with chitosan-RGD composite coating layer
CN106693051A